The Field-Dependent Rheological Properties of Magnetorheological Fluids Featuring Plate-Like Iron Particles - Shah, Kruti; Choi, Seung-Bok (Frontiers in Materials, 2014)
This study is concerned with an investigation of the plate-like iron particles based MR suspensions under the application of magnetic fields to ascertain the influence of particle size in the rheological performance. A novel synthesis route to prepare magnetorheological fluid (MRF) using two different sizes of plate-like iron particles is described in detail. Two different kinds of MRF are then prepared and their rheological properties are presented and discussed extensively. Steady shear flow and small amplitude dynamic oscillatory measurements are carried out in the presence of magnetic field. This experimental study reveals and highlights the importance of exploiting some parameters such as magnetic field strength, effect of particle size, magneto-viscous and visco-elastic properties of the suspending fluid. The magnetization of the fluids is also performed to explain the effect of particle size in the magnetic field which is directly correlated with the yield stress. In the absence of magnetic field, the properties of fluid are isotropic and upon the application of magnetic field the magnetized particles form a strong-chain like structures in the field direction which promotes the appearance of yield stress. This material is known as smart material whose properties amend from liquid to solid immediately after applying the magnetic field. It is found from this work that the large size particle based MRF exhibits high yield stress and strong chain structuration under the applying magnetic field.